Routledge Handbook of Community Forestry - Bulkan, J.; Palmer, J.; Larson, A.M.; Hobley, M. (Routledge, 2022)
Containing contributions from academics, practitioners, and professionals, the Routledge Handbook of Community Forestry presents a truly global overview with case studies drawn from across Africa, Asia, Europe, and the Americas. The Handbook begins with an overview of the chapters and a discussion of the concept of community forestry and the key issues. Topics as wide-ranging as Indigenous forestry, conservation and ecosystem management, relationships with industrial forestry, trade and supply systems, land tenure and land grabbing, and climate change are addressed. The Handbook also focuses on governance, looking at the range of approaches employed, including multi-level governance and rights-based approaches, and the principal actors involved from local communities and Indigenous Peoples to governments and national and international non-governmental organisations. The Handbook reveals the importance of the historical context to community forestry and the effects of power and politics. Importantly, the Handbook not only focuses on successful examples of community forestry, but also addresses failures in order to highlight the key challenges we are still facing and potential solutions.